An assessment of fish culture promoted by the Family Food Production Project in southeast Cambodia - Heng Socheath; Edwards, Peter; Demaine, Harvey; Little, David C.; The Government of Ne w Zealand (Bangkok : Asian Institute of Technology, 1994)
Fish is the traditional source of animal protein in the Cambodian diet but per caput fish consumption has declined drastically in recent years due to population growth, overfishing and environmental degradation. Attempts are being made to introduce fish culture to rice farmers through the Family Food Production Program (FFP), a joint activity between the Cambodian Government a nd UNICEF. This study interviewed 134 households to identify the constraints to, and opportunities for, fish culture by rice farmers under the FFP project in Svay Ri e ng and Prey Veng provinces, southeast Cambodia. There were five groups of respondents. Group 1, respondents who stocked fish before 1993 and continued to stock fish in 1993; Group 2, respondents who stocked fish before 1993 but gave up the fish culture ; Group 3, respondents who n ever stocked fish; Group 4 , respondents who never stocked fish be fore but stocked fish in 1993 for the first time a nd Group 5, respondents who owned a newly co n structed pond in 1993. The respondents ' perception of wild fish stock was of decreasing a mounts , providing a stimulus for aquaculture development. Although there is increasing intention to raising fish, lack of knowledge, shortage of fish seed at the village level and the predation of small-sized seed emerged as key factors restricting the development of fish culture under t he project. Farmers sought information but there was a lack of manpower at district and communal l eve l to transfer proper information to the respondents. A belief of death of tilapia in pond mud during thunder storms was prevalent in the thoughts of the respondents. However l about was not a major constraint . A certain number of respondents began Pangasius fish culture as they have learnt of the success of fish farmers from neighboring Vietnam. Respondents in Group 2 ceased to release fish due to failure of the previous crop ; as a result of l ack of knowledge and motivation , they did not get an attractive return from fish culture and thus were reluctant to continue. Respondents in Group 3 had n ever stocked fish because of lack of cash to purchase seed and awaiting free seed from FFP. Respondents in Group 4 began fish culture for the first time in 1993 because they were given free seed by FFP a nd were interested in Pangasius as they had seen the success of local Vietnamese fish farmers . Respondents in Group 5 with a newly constructed pond were mainly constrained by muddy water to start fish culture . fish seed distribution at no cost was not a good practice of aquaculture development . The feasibility of fish culture to provide a subsidiary job to supplement household consumption was suggested by respondents . Technical advice and fish seed availability were the most common needs to be resolved for all groups of respondents. Group 3 who never stocked fish needed more consideration for financial support and motivation while Group 5 who owned a newly constructed pond required specific technical -iii- input to c l ear muddy pond water as a first step prior to commencing other fish farming activities. The r e was a good opportunity for further promotion of fish culture as respondents had a n alternative water supply for domestic consumption from dug-well. Respondents derived only s mall benefits from fish ponds suggesting t he weakness of aquaculture development under FFP. However, FFP has offered a useful resource to farmers in terms of assisting the poor to possess an individua l house hold fish pond and t h is would be o f great value for further promotion o f fish farming whenever the farmers are in a position to proceed .
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Science, School of Environment, Resources & Development
Thesis (M.Sc.) - Asian Institute of Technology, 1994
Keywords: Fish-culture -- Cambodia